Back Cover: Retention of Native Protein Structures in the Absence of Solvent: A Coupled Ion Mobility and Spectroscopic Study (Angew. Chem. Int. Ed. 45/2016). Issue 45 (8th September 2016) - Seo, Jongcheol; Hoffmann, Waldemar; Warnke, Stephan; Bowers, Michael T.; Pagel, Kevin; von Helden, Gert
Abstract : Electrospray ionization is routinely used to release proteins into the gas phase, but it is still not clear how much of the native structure can be retained. In their Communication onpage 14173 ff., G. von Helden and co‐workers present the results of a combination of ion‐mobility mass spectrometry and IR spectroscopy techniques, which indicate that, under gentle instrument conditions, gas‐phase protein ions can resemble their solution equivalents in terms of tertiary and secondary structure.